Did the Zurich Consensus create the possibility of future dialogue with Wittenberg?. Issue 1 (2nd January 2016) - Zachman, Randall C.
Abstract : The question considered here will be whether the Zurich Consensus represent Calvin's unsuccessful attempt to reconcile the churches of Wittenberg, Strasburg, Geneva, and Zurich. Calvin expressed the hope throughout his ministry that the divisions in the evangelical movement could be overcome, and claimed to be willing to do all he could to insure that this might happen. He was convinced that the proper way to respond to genuine disagreements between servants of the gospel was not to engage in contentious disputation, but rather to pursue open-ended dialogue in pursuit of the truth. There is no doubt that Calvin followed his proposed method of dialogue in arriving at the consensus between the churches of Geneva and Zurich embodied in the Zurich Consensus. This discussion will show that by this time, Calvin seems to exclude the possibility of any future accord with Wittenberg by both the contentious way the Consensus is formulated and his interactions with Wittenberg theologians.